Enhancing the use of phosphate rock through microbially-mediated compost transformation to improve agronomic and economic profitability in Sub-Saharan Africa - Sagnon, Adama; Traore, Mamoudou; Tibiri, Ezechiel Bionimian; Zongo, Saïdou; Bonkoungou, Isidore Juste O.; Nakamura, Satoshi; Barro, Nicolas; Tiendrebeogo, Fidele; Sarr, Papa Saliou (Frontiers in Sustainable Food Systems, 2024)
Soil degradation and limited access to chemical fertilizers partly explain the persistently low crop yields in sub-Saharan Africa. To provide local farmers with alternative fertilizer options, this study examined the impact of locally sourced fertilizers on sorghum productivity and soil health. Treatments were set up in a completely randomized block design with five replications each. These treatments included Burkina phosphate rock (BPR), calcined BPR (Cal-BPR), triple super phosphate (TSP), four types of phosphocomposts, and an unfertilized phosphate control (Control). The phospho-composts, prepared during four months in advance, were as follows: Comp-1 (sorghum straw + BPR + sorghum rhizosphere soil and roots), Comp-2 (sorghum straw + Cal-BPR + sorghum rhizosphere soil and roots), Comp-3 (sorghum straw + BPR + chicken manure), and Comp-4 (sorghum straw + Cal-BPR + chicken manure). They were applied at a rate of 2.5 t ha -1 at sowing, alongside BPR, Cal-BPR, and TSP that provided 23 kg P2O5 ha -1 . Urea and potassium chloride were added 15 days after sowing (DAS) to all treatments to standardize nitrogen and potassium levels to 37 kg N ha -1 and 14 kg K2O ha -1 . Soil properties were evaluated using the samples collected at 42, 70, and 120 DAS. Rhizosphere soil showed higher bacterial and fungal abundance than bulk soil, particularly in compost treatments. Comp-4 notably improved soil properties, including increased phosphorus-cycling microbial genes, available phosphorus, cation exchange capacity, and pH, and it produced the highest sorghum grain yield. However, Comp-3 offered superior economic benefits, with higher net returns from grain sales. Overall, phosphocomposts improve soil health and boost sorghum yield in sub-Saharan Africa. Calcined BPR-chicken manure-enriched compost may be used to increase crop yields. However, the study shows that BPR-chicken manure-enriched compost provides a more cost-effective solution for soil revitalization and sustainable food production in infertile soils in the region.